ENTERPRISE ARCHITECTURE REVIEW - Florez Fernandez, Hector Arturo (Revista Vínculos, 2010)
Enterprise architecture is considered a tool that can identify the main components of the information systems in an organization. It also helps to plan how these components can work together to reach the business goals defined by the organization’s management.